(untitled) (European Bison Conservation Newsletter, 2018)
Presented is the history of reintroduction program for European bison (Bison bonasus) initiated since 1963 in Carpathian countries (Poland, Slovakia, Romania and Ukraine), including the development of particular subpopulations and genetic parameters. Discussed are reasons for the success of reintroduction in Bieszczady Mountains, Poland. Finally, indicated are drawbacks of actions undertaken in this region, and suggested are possibilities for their mitigation.